2021
DOI: 10.1590/1414-431x2020e10837
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic circDHTKD1 promotes tumor growth and metastasis of oral squamous cell carcinoma in vitro and in vivo via upregulating miR-326-mediated GAB1

Abstract: Circular RNAs (circRNAs) have been extensively elucidated with regard to their significant implications in oral squamous cell carcinoma (OSCC). This study performed the functional investigation of circRNA dehydrogenase E1 and transketolase domain containing 1 (circDHTKD1) in OSCC. RNA expression levels of different molecules were measured via quantitative real-time polymerase chain reaction (qRT-PCR). Cellular behaviors were detected by 3-(4, 5-dimethylthiazol-2-y1)-2,5-diphenyl tetrazolium bromide (MTT) for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…After reviewing the full‐text articles, 56 records were excluded whose data were insufficient and six were removed with no relevant outcomes reported (Table ). In total, 1813 OSCC patients from 26 studies were finally included in the meta‐analysis (Chen et al, 2020; Chen et al, 2020; Chen et al, 2021; Chen et al, 2018; Dou et al, 2020; Dou et al, 2019; Gao et al, 2020; Hao et al, 2020; Jiang et al, 2021; Li et al, 2021a; Liu et al, 2021; Luo et al, 2020; Ouyang et al, 2018; Peng et al, 2020; Qian et al, 2021; Qian et al, 2021; Wang et al, 2020; Wu et al, 2021; Xia et al, 2019; Yang et al, 2020; Yang et al, 2021; Yao et al, 2020; Zeng et al, 2021; Zhang et al, 2021; Zhao et al, 2020; Zhu et al, 2020). Among these articles, 19 had data related to prognostic analysis, and 22 articles reported information required for clinicopathological analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the full‐text articles, 56 records were excluded whose data were insufficient and six were removed with no relevant outcomes reported (Table ). In total, 1813 OSCC patients from 26 studies were finally included in the meta‐analysis (Chen et al, 2020; Chen et al, 2020; Chen et al, 2021; Chen et al, 2018; Dou et al, 2020; Dou et al, 2019; Gao et al, 2020; Hao et al, 2020; Jiang et al, 2021; Li et al, 2021a; Liu et al, 2021; Luo et al, 2020; Ouyang et al, 2018; Peng et al, 2020; Qian et al, 2021; Qian et al, 2021; Wang et al, 2020; Wu et al, 2021; Xia et al, 2019; Yang et al, 2020; Yang et al, 2021; Yao et al, 2020; Zeng et al, 2021; Zhang et al, 2021; Zhao et al, 2020; Zhu et al, 2020). Among these articles, 19 had data related to prognostic analysis, and 22 articles reported information required for clinicopathological analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐two studies consisting of 1506 cases and involved with twenty‐two circRNAs (hsa_circ_0001874, hsa_circ_0001971, circ‐MMP9, circ_0001742, ciRS‐7, circ‐ABCB10, circRNA_002178, circUHRF1, circEPSTI1, circ_0000199, circ_BICD2 7, circ‐LRP6, circVAPA, circHIPK3, circBCL11B, circDHTKD1, circ_0000003, hsa_circ_0092125, circATRNL1, circ_0000140, circ‐ITCH, and Hsa_circ_0043265) were enrolled in the meta‐analysis of clinicopathological parameters (Chen et al, 2020; Chen et al, 2020; Chen et al, 2021; Chen et al, 2018; Dou et al, 2020; Gao et al, 2020; Hao et al, 2020; Jiang et al, 2021; Luo et al, 2020; Peng et al, 2020; Qian et al, 2021; Qian et al, 2021; Wang et al, 2020; Wu et al, 2021; Xia et al, 2019; Yang et al, 2020; Yao et al, 2020; Zeng et al, 2021; Zhang et al, 2021; Zhao et al, 2020; Zhu et al, 2020). The correlations between circRNAs expression and OSCC clinicopathological characteristics (including age, gender, tumor site, histological differentiation, lymph node metastasis, distant metastasis, TNM stage, and tumor stage) were presented in Table ( p < 0.05 suggests statistical significance) which indicated that all of the twenty‐two circRNAs were related to at least one clinicopathological parameters (e.g., TNM stage).…”
Section: Resultsmentioning
confidence: 99%
“…GAB1 is frequently aberrant in cancerous tissues and cells, and is related to OSCC progression. 16 It has been previously reported that repressed GAB1 can affect B-cell receptor signaling in chronic lymphocytic leukemia. 28 Upregulated GAB1 facilitates breast cancer metastasis via dissociation of the polarity-associated partitioning defective (PAR) complex.…”
Section: Discussionmentioning
confidence: 98%
“…Having revealed the vital function of miR‐126‐5p in the suppression of OSCC progression, the potential mechanisms were then explored. GAB1 is frequently aberrant in cancerous tissues and cells, and is related to OSCC progression 16 . It has been previously reported that repressed GAB1 can affect B‐cell receptor signaling in chronic lymphocytic leukemia 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation